Effects of three months of water-based exercise training on metabolic syndrome components in older women (Efecto de tres meses de entrenamiento con ejercicios acuáticos sobre componentes del síndrome metabólico en adultas mayores) - Ochoa-Martínez, Paulina Yesica; Hall-López, Javier Arturo; Piña Diaz, Daniel; Zarate Trujillo, Diego Armando; Teixeira, Ana Maria (Retos, 2019)
Abstract. The purpose of this study was to evaluate the effects of water-based exercise training on metabolic syndrome components in older women. The subjects were randomly divided into an experimental group who participated in the water-based exercise training and a control group who was not involved in the training and remained sedentary. The quantification of clinical and biochemical parameters of abdominal obesity, atherogenic dyslipidemia, elevated blood pressure and insulin resistance without glucose intolerance by a medical and laboratory evaluation to assess the presence of metabolic syndrome components was done according to the guidelines of the National Cholesterol Educational Program Adult Treatment Panel-III (NCEP ATP-III). The training protocol consisted of water-based exercise training sessions 5 times per week during 12 weeks of intervention, executed in a pool of 1.3 meters divided into three phases: a 10-minute warm-up, 30 minutes of aerobic exercise at 50%-60% of maximum heart rate (monitored by heart rate monitor) and a 10 minute cool down. As a statistical method to compare the results between groups of variables pre and post training, the statistical analysis ANOVA mixed 2 X 2 (group X measurement) was done using SPSS version 21. The results for the metabolic syndrome components only indicated statistically significant interactions for triglycerides mg.dl-1 (p=0.002) between the groups and the measurements. Thus, the training program produced significant benefits on metabolic health indicators in particular decreasing triglycerides. Resumen. Objetivo: Evaluar los efectos del entrenamiento con ejercicio acuático sobre los componentes del síndrome metabólico en adultas mayores. Los participantes se dividieron en un grupo experimental y un grupo control que permaneció sedentario. La presencia de componentes del síndrome metabólico se evaluó de acuerdo con las directrices del Programa Nacional de Educación en Colesterol (NCEP–III) que evalúa los parámetros clínicos y bioquímicos de obesidad abdominal, dislipidemia aterogénica, presión arterial y resistencia a la insulina sin intolerancia a la glucosa. El protocolo de entrenamiento consistió en sesiones 5 veces por semana durante 12 semanas, divididas en tres fases: calentamiento 10 minutos, 30 minutos de ejercicio aeróbico al 50% -60% de la frecuencia cardíaca máxima y relajación 10 minutos. Como método estadístico para comparar los resultados entre grupos de variables pre y post, se realizó el análisis de varianza (ANOVA) mixta 2 X 2. Los resultados en los componentes del síndrome metabólico solo indicaron interacciones estadísticamente significativas para los triglicéridos mg.dl-1 (p=0.002) entre los grupos y las mediciones. Por lo tanto, el programa de entrenamiento resulto beneficioso sobre los indicadores de salud metabólica, en particular la disminución de triglicéridos.